The effects of Mary Rose conservation treatment on iron oxidation processes and microbial communities contributing to acid production in marine archaeological timbers. - Joanne Preston; Andrew D Smith; Eleanor J Schofield; Alan V Chadwick; Mark A Jones; Joy E M Watts (PLoS ONE)
The Tudor warship the Mary Rose has reached an important transition point in her conservation. The 19 year long process of spraying with polyethylene glycol (PEG) has been completed (April 29(th) 2013) and the hull is air drying under tightly controlled conditions. Acidophilic bacteria capable of oxidising iron and sulfur have been previously identified and enriched from unpreserved timbers of the Mary Rose, demonstrating that biological pathways of iron and sulfur oxidization existed potentially in this wood, before preservation with PEG. This study was designed to establish if the recycled PEG spray system was a reservoir of microorganisms capable of iron and sulfur oxidization during preservation of the Mary Rose. Microbial enrichments derived from PEG impregnated biofilm collected from underneath the Mary Rose hull, were examined to better understand the processes of cycling of iron. X-ray absorption spectroscopy was utilised to demonstrate the biological contribution to production of sulfuric acid in the wood. Using molecular microbiological techniques to examine these enrichment cultures, PEG was found to mediate a shift in the microbial community from a co-culture of Stenotrophomonas and Brevunidimonas sp, to a co-culture of Stenotrophomonas and the iron oxidising Alicyclobacillus sp. Evidence is presented that PEG is not an inert substance in relation to the redox cycling of iron. This is the first demonstration that solutions of PEG used in the conservation of the Mary Rose are promoting the oxidation of ferrous iron in acidic solutions, in which spontaneous abiotic oxidation does not occur in water. Critically, these results suggest PEG mediated redox cycling of iron between valence states in solutions of 75% PEG 200 and 50% PEG 2000 (v/v) at pH 3.0, with serious implications for the future use of PEG as a conservation material of iron rich wooden archaeological artefacts.